Investigation of the bioavailability of radiocesium in the Fukushima exclusion zone using a sequential extraction technique - McNabb, Ian, author; Sudowe, Ralf, advisor; Johnson, Thomas, committee member; Borch, Thomas, committee member (Colorado State University. Libraries, 2019)
The nuclear reactor accident at the Fukushima Daiichi power plant in March of 2011, resulted in the release of large quantities of various radionuclides into the environment. The main radionuclide of concern still remaining today is cesium-137 due to its 30-year half-life. Several areas in the vicinity of the power plant are still considered an exclusion zone owing to contamination with radiocesium, and they have not been cleared for human resettlement. While these parts are not suitable for permanent habitation, they are accessible for field work. The purpose of this research was to analyze the movement and bioavailability of radiocesium in the ecosystems contaminated by fallout from the Fukushima Daiichi nuclear reactor accident. This was achieved by analyzing soil cores collected from within the exclusion zone. The core samples were run though a 5-step sequential extraction technique, which exposes the soils stepwise to an increasingly aggressive chemical treatment. Each step targets a specific soil host phase: exchangeable, carbonate bound, Fe/Mn bound, organic, and residual. The results of this extraction yielded the following distribution of Cs-137 activity (percent of total): 0% exchangeable, 1-16% carbonate bound, 0-5% Fe/Mn bound, 1-5% organic, 44-67% residual, and 25-47% non-extracted. These results show that most of the Cs-137 is irreversibly bound to clays in the soil. However there are differences between soil sampling sites in regards to the amount of Cs-137 successfully extracted in the carbonate bound, Fe/Mn bound, and Organic fraction, which provides evidence that Cs-137 mobility and bioavailability is partly dependent on local soil mineralogy and chemistry.